A defense of holistic representationalism. (4th January 2018) - Berger, Jacob
Abstract : Representationalism holds that a perceptual experience's qualitative character is identical with certain of its representational properties. To date, most representationalists endorse atomistic theories of perceptual content, according to which an experience's content, and thus character, does not depend on its relations to other experiences. David Rosenthal, by contrast, proposes a view that is naturally construed as a version of representationalism on which experiences' relations to one another determine their contents and characters. I offer here a new defense of this holistic representationalism, arguing that some objections to atomistic views are best interpreted as supporting it.